INFORMATION TECHNOLOGIES AS COMPONENT OF FUNCTIONAL AND SUBSTANTIAL MODEL OF FORMATION PREDICTIVECOMPETENCE OF FUTURE MASTERS OF PRIMARY EDUCATION - Anastasia Kinesheva (Kherson State University, 2015)
Considerd the structure and the maintenance of the model of formation of predictive competence of future masters of primary education by means of information technologies.Revealed the purposes, the main methodological approaches and the principles to the organization of this process. The effectiveness of this model provided by the system of pedagogical conditions: formation of motivational-value treatment to future predictive activity; determination of understanding the existing dependence between the level of predictive competence and level of the general professional competence of future masters of primary education through introduction of a special course «Predictive activity in system of management of primary education»; innovative information and communication the educational environment; integration of a special course «Predictive activity in system of management of primary education», production, pre-graduation practices. The realization of the specified pedagogical conditions is planning to enable due to specially created information and education environment, presented by innovative forms, methods and means which are relative. Defined the following structural components (motivational-value, pregnant, technological and personal), criteria (motivational-value, cognitive, operational-activity, reflexive), the indicators and levels (advanced, sufficient and basic) formation of predictive competence of future masters of primary education. The educational process constructed on the basis of this model allows to reach desirable result: to create predictive competence at future masters of primary education.